Facebocrastination? Predictors of using Facebook for procrastination and its effects on students' well-being - Meier, Adrian; Reinecke, Leonard; Meltzer, Christine E. (Computers in Human Behavior, 2016)
Procrastinating with popular online media such as Facebook has been suggested to impair users' wellbeing, particularly among students. Building on recent procrastination, self-control, and communication literature, we conducted two studies (total N = 699) that examined the predictors of procrastination with Facebook as well as its effects on students' academic and overall well-being. Results from both studies consistently indicate that low trait self-control, habitual Facebook checking, and high enjoyment of Facebook use predict almost 40 percent of the variance of using Facebook for procrastination. Moreover, results from Study 2 underline that using Facebook for the irrational delay of important tasks increases students' academic stress levels and contributes to the negative well-being effects of Facebook use beyond the academic domain. The implications of investigating procrastination as a specific pattern of uncontrolled and dysfunctional media use are discussed with regard to research on the uses and effects of ubiquitous online media. (C) 2016 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-02-02
Keywords: Facebook; procrastination; self-control; social network sites; university students; well-being